2014
DOI: 10.2105/ajph.2014.302195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Transparent Reporting of Evaluations With Nonrandomized Designs Reporting Guideline: Ten Years On

Abstract: TREND appeared to be underutilized by authors and journal editors despite its potential application and benefits. We found evidence that suggested that using TREND could contribute to more transparent and complete study reports. Even when authors reported using TREND, reporting completeness was still suboptimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
0
26
0
2
Order By: Relevance
“…Chi‐square tests of association indicated that studies that had used TREND were more likely to have higher study quality ratings than those that had not used it. The results provide some evidence that using TREND improves the completeness of reports of studies with non‐randomised designs (Fuller et al., ). However even when using a “generous” coding standard to determine whether an item was reported or not, there were still suboptimal levels of reporting completeness.…”
Section: Studymentioning
confidence: 75%
See 1 more Smart Citation
“…Chi‐square tests of association indicated that studies that had used TREND were more likely to have higher study quality ratings than those that had not used it. The results provide some evidence that using TREND improves the completeness of reports of studies with non‐randomised designs (Fuller et al., ). However even when using a “generous” coding standard to determine whether an item was reported or not, there were still suboptimal levels of reporting completeness.…”
Section: Studymentioning
confidence: 75%
“…We found that the average reporting completeness of papers that had used the TREND guideline was 75% [95% CI 72–77] compared with 65% [95% CI 62–68] with studies that had not used TREND (Fuller, Peters, Pearson, & Anderson, ). Chi‐square tests of association indicated that studies that had used TREND were more likely to have higher study quality ratings than those that had not used it.…”
Section: Studymentioning
confidence: 99%
“…Sin embargo, la evidencia al respecto es contradictoria 18,19 , lo que puede estar influenciado por múltiples factores. En cualquier caso, la utilidad de estas herramientas cuando son utilizadas correctamente a lo largo de la preparación de los manuscritos es innegable.…”
Section: Discussionunclassified
“…The sixth step consisted of evaluating the methodological quality, using the PEDro 15,16 scale for RCTs and the TREND (Transparent Reporting of Evaluations with Nonrandomized Designs) scale 17,18 for the QE studies. The PEDro scale is composed of 11 items, each item contributing with 1 point (except for item 1 that is not punctuated) and the final score ranges from 0 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…16 The TREND school is a guideline composed of 23 items, each item contributing with one point to the total score, but there are still no determined criteria to classify the final score of this scale. 17,18 Finally, the seventh and last stage involving the data extraction was performed. In order to meet the objectives of this systematic review, the following data were extracted from the included studies: population studied, type of physical exercise performed, intervention protocol, variables analyzed, method of measuring the outcomes, conclusion and results.…”
Section: Methodsmentioning
confidence: 99%